Keanekaragaman Jenis Pakan Lebah Madu Hutan (Apis dorsata) di Amfoang (Studi Kasus di Hutan Produksi Desa Soliu, Kecamatan Amfoang Barat Laut, Kabupaten Kupang, Provinsi Nusa Tenggara Timur) - Wengki Kuanine; Maria M. E. Purnama; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Forest is an ecosystem unit in the form of an expanse of land containing biological natural resources dominated by trees in their natural environment which cannot be separated from one another, if it has been changed or damaged the continuity of the ecosystem in the forest will be damaged and no longer has a balance of existing ecosystems. This study aims to determine the level of composition of honey bee forage species and the diversity of honey bee forage species in production forests in Northwest Amfoang, Soliu Village.The type of composition of forest honey bee forage species found in the Soliu Village Research Forest, Northwest Amfoang District, consists of 15 types of honey bee forage with a total of 622 individuals.The level of species diversity (H') of forest honey bee forage species in the production forest area of Soliu Village, Northwest Amfoang District. for each level is classified as moderate, namely at the tree level of 2.20% including moderate criteria, poles of 2.35% and including moderate criteria, saplings of 1.54% including moderate criteria and seedlings reaching 0,70% and including low criteria.